2005
DOI: 10.1111/j.1537-2995.2006.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

The how and why of exocytic vesicles

Abstract: The purpose of this review is to draw the attention of general readers to the importance of cellular exocytic vesiculation as a normal mechanism of development and subsequent adjustment to changing conditions, focusing on red cell (RBC) vesiculation. Recent studies have emphasized the possible role of these microparticles as diagnostic and investigative tools. RBCs lose membrane, both in vivo and during ex vivo storage, by the blebbing of microvesicles from the tips of echinocytic spicules. Microvesicles shed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(165 citation statements)
references
References 149 publications
(259 reference statements)
8
156
0
1
Order By: Relevance
“…However, our data suggest that these structures would only represent a small proportion of sMHC in blood. Maturing reticulocytes have been shown to produce exosomes or microvesicles in vitro and storage of blood products leads to the release of microvesicles, though this may depend on the choice of anticoagulant used (see [10] for recent review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our data suggest that these structures would only represent a small proportion of sMHC in blood. Maturing reticulocytes have been shown to produce exosomes or microvesicles in vitro and storage of blood products leads to the release of microvesicles, though this may depend on the choice of anticoagulant used (see [10] for recent review).…”
Section: Discussionmentioning
confidence: 99%
“…Exosome release appears to be a consequence of normal cellular programs such as differentiation and antigen processing [8][9][10][11]. It has been reported that exosomes secreted by APC contain large amounts of MHC class I (MHC-I) and II (MHC-II) molecules, as well as detectable levels of certain costimulatory molecules [8,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of MDA decreased in controls towards the end of storage, indicative of the effective antioxidant system in the erythrocytes. The decrease in MDA can also be attributed to microvesiculation which occurs in vitro [53] In the L-carnitine groups, peaks were observed on day 5 due to increase in ROS. The decrease in MDA in the LC groups to the control levels can be attributed to the combined effect of the initial scavenging of free radicals by L-carnitine [54] and the inherent antioxidant system of the erythrocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, microvesicles from stored red blood cells are shed in relatively greater numbers toward the end of storage when ATP concentrations are low [31]. These vesicles expose negatively charged phospholipids on their surfaces that are potentially proinflammatory and procoagulant.…”
Section: Are Stored Red Blood Cells Safe?mentioning
confidence: 99%